Políticas municipais de prevenção à violência no Brasil : desafios e experiências no campo da segurança pública - Spaniol, Marlene Inês (2016)
This thesis investigated municipal prevention policies against violence in Brazil, the challenges encountered in their implantation and some specific public safety experiences, i.e. in the municipalities of Diadema, in the state of São Paulo, and in Canoas, in the State of Rio Grande do Sul, which were the first to innovate in this domain, showing good results in criminal occurrences, in creating a closer relationship with the community and in integrating federal, state and municipal bodies. Furthermore, the thesis aimed at discussing the changes that have been thought, debated and presented to modify the public safety system in Brazil before, during and after the Federal Constitution‟s entry into force in 1988. The importance of offering public safety services oriented towards the exercise of citizenship, in an integrated way between police and community bodies, was also discussed. Municipalities that implemented prevention public policies against violence through the Integrated Management Offices (GGI, in Portuguese) were especially highlighted. Bibliographical review was presented in a chapter focusing on violence, public safety and democracy, on how they developed throughout Brazilian history until nowadays, as well as on public safety management and public policies concerning this topic, analyzing their development in Brazil. Another chapter aimed at presenting the Uruguayan model of public safety, as a result of a PhD research period, looking for similarities and divergences in the adoption of safety policies between these two countries. As far as municipal prevention policies against violence were concerned, the role of local management power was investigated: in order to achieve this goal, the analysis of these two violence prevention experiences was carried out, the main criminality indicators - before, during and after its implementation - were collected and local, state and national managers in the field were interviewed through the Ministry of Justice and the National Secretariat for Public Safety (SENASP, in Portuguese). The main goal was to answer the following research question: why is it so difficult to consolidate these experiences in Brazil, despite the consensus over the importance of the role of municipalities and of prevention policies against violence in the field of public safety? The conclusion pointed out that these changes do not occur because there is an established public safety model that confers all the power to police corporate structures and, according to them, it is not sure that this change would be positive. Furthermore, considering how municipalities are recognized in the Constitution, in the article concerning public safety, these bodies do not have direct responsibility in this field. Nevertheless, the several Proposals for Constitution Amendment (PEC, in Portuguese) related to this topic show the difficulty in altering any provision referring to the current national public safety system. In Brazil, consolidation of municipal violence prevention experiences has proven to be very difficult, being limited to specific and voluntary-based examples, or to cases dictated by the affinity of local managers with the topic, as in the two examples observed in Diadema/SP and in Canoas/RS.